History of the Jewish of Doumna in the Othoman Empire - Al-Ahmed, Abd Al –Moneim; Ali, Sahar (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
Doumna : a term that is heard mostly, but majority of people have no idea about its literal meaning , when did it arise ? how and what are the reasons of its inception ? The term Doumna is originally derived from the Persian language , which means " two " , nma ( two types ) . Although their followers converted to Islam , they remained faithful to their Judaism secretly as religion , ideology and political thought. This search will illustrate who are the Jews of Doumna as a Zionist Jewish community that appeared in 1664 AD , due to the persecution and expulsion from Europe that they had faced during the reign of the king , Ferinand of Spain . In addition to their role in the Othoman Empire , starting with the appointment of the Othoman Sultans to their isolation . Also , their role in running the affairs of the country especially the financial ones because they were professionals and experts in the field of trade and banking . Finally , the Jewish of Doumna are the true founders of the Zionist movement and the idea of making Palestine a national homeland for them .